PENGARUH PERCEIVED VALUE, KEPERCAYAAN, KEMUDAHAN PENGGUNAAN, E-WOM TERHADAP LOYALITAS PELANGGAN DIMEDIASI KEPUASAN - Fitri Susilowati; Nurjanah; Adhi Prakosa (UNIVERSITAS PGRI MADIUN, 2025)
Through customer satisfaction, this study was conducted to examine how perceived value, trust, ease of use, and electronic word of mouth affect Shopee customer loyalty. Purposive sampling was used to pick 100 respondents from Shopee customers in Special Region of Yogyakarta. The Structural Equation Model (SEM) on SmartPLS version 4 application used to analyze data. The results revealed that electronic word of mouth hasn’t influence customer satisfaction, however perceived value, trust, and ease of use significantly increase consumer satisfaction. Customer loyalty is significantly positively impacted by the variables of trust, ease of use, and customer satisfaction, but not impacted by perceived value and electronic word of mouth. Customer satisfaction in this research not able to mediate the relationship between perceived value and electronic word of mouth on Shopee customer loyalty. However, customer loyalty is significantly impacted by customer satisfaction